Firm performance: an empirical study on timeliness of financial reporting and financial voluntary disclosure / Norziaton Ismail Khan and Nor Hidayah Abd Rahim - Ismail Khan, Norziaton; Abd Rahim, Nor Hidayah (2016)
Timeliness of financial reporting is an essential part in determining the relevance of accounting information while disclosure is another important element for decision making purposes by the financial reporting information users. This study has two (2) objectives. The first objective investigates a relationship between timeliness of financial reporting and firm performance. Where else, second objective examines a relationship between financial voluntary disclosure and firm's performance. This research draws from agency theory, to form a framework and develop the hypotheses to be examined. Two hypotheses are developed and tested using data from 98 sample firms from years 2011, 2012 and 2013 which is equivalent to 294 firm's year observation. The findings show that timeliness of financial reporting has significant relationship with firm's performance. It indicates that less number of days in announcing the annual report could increase the firm's performance. However, financial voluntary disclosure has insignificant relationship with firm's performance, indicating that the financial voluntary disclosure items disclosed in the annual report have insignificant impact on firm performance. Overall, this study has highlighted on the importance of timeliness of financial reporting as to assist shareholders in making decision effectively for their future investments.